Causes and management of post-partum hemorrhage at tertiary care center, Rajasthan, India - Gora, Kamlesh; Depan, Anju; Yadav, Kanti; Benwal, Devendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: PPH is responsible for 25% of all maternal deaths. In India, PPH incidence in India is 2%-4% following vaginal delivery and 6% following cesarean section. PPH as the important cause of 19.9% of maternal mortality in India. The objectives of the study were to study the incidence, risk factors, cause, morbidity and mortality pattern and management of PPH. Methods: This is a cross-sectional study conducted among 102 pregnant women selected by convenient sampling and admitted in labour room during the study period who will be deliver by vaginally or by caesarean section. The patient having PPH were divided into two groups: Group I: Patients having primary atonic PPH, Group II: Patients having traumatic PPH. Results: Mean age of participants was 33.6 and 32.9 years, 59.3 and 51.2 have ‘0’ parity, mean BMI 22.8 and 23.9 kg/m2, 34.6% and 17.1 babies were delivered by LSCS, 11.7% and 12.2% have history of PPH in the group of atonic and traumatic respectively. In the group of atonic PPH cases, 77.2%, 15.4%, 4.3% and 3.1% cases managed by the method of ‘Uterotonics +<2 blood transfusions’, ‘Uterotonics + >2blood transfusions’, ‘Perineal Tear Repair’ and ‘Surgical Intervention’ respectively. All the traumatic PPH cases (100.0%) were managed by ‘surgical intervention’. Conclusions: A multi-disciplinary approach include medical, mechanical, surgical and radiological is required in severe haemorrhage. Availability of blood and blood products is very crucial. Prediction and assessment of blood loss and timely identification of uterine atony are remaining the cornerstone for prompt and effective management of PPH.